Quantificação das emissões de gases de efeito estufa para veículos de coleta de resíduos domiciliares abastecidos com GNV e Diesel-B5 utilizando avaliação de ciclo de vida (ACV) - Costa, Ronaldo Silvestre da (2016)
The transport sector represents a significant responsibility in the pollution emissions. Also, the consumption of fossil fuels is related with the rising of global average temperature due to the greenhouse gas emissions. Biofuels and natural gas are investigated as alternative fuels to mitigate the environmental impacts. However, due to the several source emissions within a product life-cycle, the environmental performance of an environmental friendly product must be verified. This work aims to quantify greenhouse gas emissions during household waste collection by heavy vehicles (trucks) fueled with different fuels. It was proposed the development and implementation of a methodology to compare both pollutant gas emissions and noise for the use of CNG (compressed natural gas) and diesel-B5, aiming to mitigate environmental impacts in captive fleet that travels daily in the Porto Alegre city, Rio Grande do Sul state, Brazil. The trucks were monitored using a portable gas analyzer equipment (O2, CO, CO2, NO, NO2, NOx, SO2, HC), and the fuel consumptions and autonomy were obtained from the company that provides the service. With the data collected on established routes, it was applied the Life Cycle Assessment (LCA) methodology to carry out the study comparing the environmental performance of the use of CNG and Diesel-B5. The results showed that higher global warming impact (according IPCC method) was observed to CNG, independently of the time horizon considered (20 100 or 500 years). When comparing the contribution of the process stages (from production to use of fuels), CNG presented higher impacts in the collection and venting steps, while diesel -- B5 presented in the collection step.